2024
DOI: 10.1186/s13690-023-01234-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in emergency department visits and mortality during the COVID-19 pandemic: a retrospective analysis of 956 hospitals

Mahya Razimoghadam,
Mehdi Yaseri,
Mohammad Effatpanah
et al.

Abstract: Background During the COVID-19 pandemic, many non-COVID-19 emergency department (ED) visits were indirectly affected. ED visits and mortality were assessed during different pandemic time periods compared with pre-pandemic. Methods The study used data from 41 million Iran Health Insurance Organization members. The outcomes were non-COVID-19 ED visits and associated mortality in 956 hospitals. An analysis of ED visits was conducted both for all-cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 88 publications
1
1
0
Order By: Relevance
“…The hospital’s shift of resources and equipment to COVID-19 patients was also likely to result in a reduction in quality of service for non-COVID patients, leading to mortality. An increase in non-COVID-19 hospital mortality rates during COVID-19 peaks and lockdowns has also been reported in other studies [ 24 , 27 , 30 , 34 , 40 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The hospital’s shift of resources and equipment to COVID-19 patients was also likely to result in a reduction in quality of service for non-COVID patients, leading to mortality. An increase in non-COVID-19 hospital mortality rates during COVID-19 peaks and lockdowns has also been reported in other studies [ 24 , 27 , 30 , 34 , 40 ].…”
Section: Discussionsupporting
confidence: 78%
“…This may be attributed to the necessity of this group’s hospital visits or to the Iranian government’s efforts to encourage childbearing. Several studies around the world also reported fewer total non-COVID hospital admissions during the first wave [ 8 , 24 40 ]. This study also demonstrated a significant decline, especially in pediatric hospital admissions during the pandemic, particularly during the first peak.…”
Section: Discussionmentioning
confidence: 99%